14‐3‐3ζ promotes gliomas cells invasion by regulating Snail through the PI3K/AKT signaling. (18th January 2019) - Li, Junjun; Xu, Hao; Wang, Qiangping; Wang, Sihua; Xiong, Nanxiang
Abstract: 14‐3‐3ζ has been reported to function as critical regulators of diverse cellular responses. However, the role of 14‐3‐3ζ in gliomas progression remains largely unknown. The expression level of 14‐3‐3ζ and Snail was detected by Western blot analysis and quantitative polymerase chain reaction in different grades of human gliomas. The effect of 14‐3‐3ζ on gliomas progression was measured using cell migration and invasion assay, the colony formation experiment, and CCK‐8 assay. The effect of 14‐3‐3ζ on PI3K/AKT/Snail signaling protein expression levels was tested by Western blotting. Firstly, 14‐3‐3ζ was often up‐regulated in high‐grade gliomas relative to low‐grade gliomas, and this overexpression was significantly related to tumor size, Karnofsky Performance Scale score and weaker disease‐free survival. Secondly, the overexpression of 14‐3‐3ζ promoted gliomas cells proliferation, migration, and invasion. Conversely, the knockdown of 14‐3‐3ζ suppressed gliomas cells proliferation, migration, and invasion. Furthermore, subsequent mechanistic studies showed that 14‐3‐3ζ could activate PI3K/AKT/ Snail signaling pathway to facilitate gliomas cells proliferation, migration, and invasion. This study shows that the overexpression of 14‐3‐3ζ can promote remarkably gliomas cells proliferation, migration, and invasion by regulating the Snail protein expression through activating PI3K/AKT signaling, and it may serve as a potential prognostic marker and therapeutic target for gliomas. Abstract : Although aberrant expression of 14‐3‐3ζ contributes to tumor progression and metastasis in a number of carcinomas, the status of 14‐3‐3ζ and its correlation with prognosis in glioma, which is a common, morbid, and frequently lethal malignancy, are still controversial. This study shows that the overexpression of 14‐3‐3ζ can promote remarkably gliomas cells proliferation, migration, and invasion by regulating the Snail protein expression through activating PI3K/AKT signaling, and it may serve as a potential prognostic marker and therapeutic target for gliomas.